The Rise of Metaverse: A Comprehensive Review of Trends, Challenges and Future Prospects (International Journal of Food and Nutritional Sciences, 2022)
The metaverse, an immersive virtual universe in which physical and digital realities converge,has emerged as a transformative pressure reshaping human interaction, era, and society. Thisreview paper delves into the evolution of the metaverse, tracing its origins and pivotaltendencies